2012
DOI: 10.1007/s00520-012-1458-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of cancer treatment summaries and care plans among Massachusetts physicians

Abstract: Interventions are needed to make treatment summaries and care plans a part of standard care for all cancer survivors. Increasing the use of treatment summaries and care plans will require specific training and reimbursement and may be facilitated by templates that capture automated data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 16 publications
6
62
1
Order By: Relevance
“…56,62 In one study, approximately half of PCPs reported never having received a treatment summary. 57 PCPs strongly recommended improved communication with oncologists so that they could effectively treat cancerrelated issues concurrently with oncologist-led treatment of the primary malignancy. 56,58,60,62,69,70 PCPs suggested improving post-treatment follow-up through a shared data management system, 53 such as the broad integration of electronic medical records and standard communication procedures between PCPs and specialists.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
See 4 more Smart Citations
“…56,62 In one study, approximately half of PCPs reported never having received a treatment summary. 57 PCPs strongly recommended improved communication with oncologists so that they could effectively treat cancerrelated issues concurrently with oncologist-led treatment of the primary malignancy. 56,58,60,62,69,70 PCPs suggested improving post-treatment follow-up through a shared data management system, 53 such as the broad integration of electronic medical records and standard communication procedures between PCPs and specialists.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
“…52 In terms of information preferences, 85-99 % of PCPs would have liked to have received additional information from oncologists regarding cancer treatments, 40,56,57 the referring PCP's role, 56 findings of investigations and likely prognosis, 56 the oncologist's follow-up plan, 56,57 clinical practice guidelines for survivorship care, 40 and potential short and long term sideeffects, including suggested management.…”
Section: Information Needsmentioning
confidence: 99%
See 3 more Smart Citations